A Librarian's Role in Improving Rigor in Research—AlzPED: Alzheimer's Disease Preclinical Efficacy Database. Issue 3 (3rd July 2017) - Sheffield, Cynthia L.; Refolo, Lorenzo M.; Petanceska, Suzana S.; King, R. James
ABSTRACT: Alzheimer's disease (AD) is debilitating and costly. The U.S. National Institutes of Health Library (NIH Library) and the National Institute on Aging have collaborated to develop a database that is focused on preclinical AD research: the Alzheimer's Preclinical Efficacy Database (AlzPED) [alzped.nia.nih.gov]. An in-depth look at the preclinical literature concerning AD demonstrates problems that can be symptomatic of the preclinical or laboratory study literature in general. There is an urgent need for better reporting within the AD research community, and this community could benefit from the skills Medical Librarians provide. Informationists and information architects can improve access to discrete and critical data while transforming research to focus on rigor and reproducibility.